Analisis Kelayakan Kredit Calon Debitur Sebagai Dasar dalam Pengambilan Keputusan Pemberian Kredit Usaha Rakyat (Studi Kasus pada PT Bank BTN Syariah) - Putri, Yusti Eka; Halmi, Halmi; Irmawati, Ika; Harun, Salmah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
The purpose of this writing is to understand and determine the Credit Worthiness Analysis of Prospective Debtors as a Basis for Making Decisions on Providing People's Business Credit (Case Study at PT Bank BTN Syariah) Makassar branch. In analyzing the data, the author uses a qualitative data analysis method as a research method that explains descriptively the Analysis of Credit Worthiness of Prospective Debtors as a Basis for Making Decisions on Providing People's Business Credit (Case Study at PT Bank BTN Syariah) Makassar branch. The result of this research is an analysis of the creditworthiness of prospective debtors as a basis for making decisions on granting people's business credit (case study at PT Bank BTN Syariah) Makassar branch which was carried out in several stages, namely the financing application stage, credit analysis stage, credit decision stage, and disbursement stage. Furthermore, the criteria for customers accepted for KUR financing are customers who pass the 5C analysis, while customers who are rejected are those who do not meet one of the 5C principles. However, in its implementation, PT Bank BTN Syariah Makassar branch prioritizes two aspects, namely character and capacity in the process. Analysis of the Credit Worthiness of Prospective Debtors as a Basis for Making Decisions on Providing People's Business Credit (Case Study at PT Bank BTN Syariah) Makassar branch.